Mobile technologies and firm formalization: Evidence from Uganda - Marina Dodlova; Krisztina Kis-Katos; Anna Kochanova; Olivia Wirth (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
We investigate how the arrival and expansion of mobile network access in Uganda influences firm tax behaviour. Access to mobile technologies could broaden government revenues from corporate income tax through the extensive margin: by reducing the costs of formalization, it could increase the number of firms filing corporate income tax. If these newly formalizing firms are also economically successful, they will contribute to the expansion of the tax base. Moreover, mobile technologies could also enhance firm performance directly, resulting in further increases in the tax base. Among the possible channels of the relationship between the use of mobile technology and tax liabilities, we examine changes in firm performance as higher firm productivity will broaden the tax base. We assess the effects of mobile technologies on firm formalization and tax outcomes using administrative tax records provided by the Uganda Revenue Authority from 2013 to 2020. We link subcounty-sector-level aggregate outcomes to the roll-out of the 3G mobile network and contrast two identification strategies to assess causal effects. We extend two-way fixed effects models by a shift-share instrumental variable strategy that predicts the local roll-out of mobile technologies based on the costs of network maintenance, proxied by local exposure to lightning. We complement those results with staggered difference-in-differences estimates. We find that the roll-out of mobile technologies increases the number of firms reporting to the tax authorities, as well as overall tax revenues. While increased formalization results in more overall sales recorded in the formal economy, firms also report substantially larger costs and deductions, which lead to higher losses that are carried forward to the next fiscal year, reducing next year's tax base.
Keywords: H25; H71; O17; 330; mobile technologies; tax behaviour; administrative records; staggered difference-in-differences; shift-share instruments; firm performance; Uganda